Effect of substrate concentration and agitation rate on butanol production from POME by Clostridium beijerinckii - Ellie Fazlin, Mohd Sarian (2010)
Palm oil mill effluent (POME) is the largest by product generated from palm oil mills, about 50 million tonnes annually. POME has a potential substrate for acetone, butanol and ethanol production using Clostridium beijerinckii. This research mainly studied on the direct use of POME as fermentation medium for solvent fermentation by Clostridium beijerinckii ATCC 51743. This research also investigated the growth profile rate and the consumption of glucose by Clostridium beijerinckii during fermentation. Fermentation were conducted for 72 hours at 370C by using palm oil mill effluent and reinforced clostridia medium as a growth medium in batch culture. Investigations were carried out on the effect of subsrate (POME) concentration and the agitation rate into the production of butanol. The POME concentration that had been used in this investigation were 90%, 80% and 70% while the agitation rate that had been used were 0 rpm, 100 rpm, 175 rpm and 250 rpm respectively. The results showed that the highest yield of butanol produced was 3.12 g/L by 70% POME at 100 rpm of agitation rate.